Impulsive Behavior and Petty Corruption in Higher Education: A Psychologically Informed Prevention Model - Sengkey, Marssel Michael; Tiwa, Tellma Monna (Indigenous: Jurnal Ilmiah Psikologi, 2026)
Petty corruption remains a persistent issue in higher education administrative services, yet its behavioral foundations are not well understood. This qualitative case study examines how impulsive behavior among administrative employees appears to be associated with petty deviations at Universitas Negeri Manado. Data were gathered through twenty-one working days of participatory observation, fifteen semistructured interviews, a focus group discussion, and document analysis. Impulsivity was examined using the Barratt Impulsiveness Scale (BIS-11), encompassing motor, cognitive, and non-planning dimensions. Motor impulsivity was associated with bypassing Standard Operating Procedures, cognitive impulsivity with emotionally driven shortcuts, and non-planning impulsivity with inconsistent workflow patterns. These behaviors were shaped by service pressure, emotional strain, relational expectations, and permissive cultural norms. The study provides a nuanced understanding of impulsivity as a proximal psychological mechanism influencing administrative decision making. A psychologically informed prevention model is proposed, emphasizing emotional regulation training, integrity-oriented cultural reinforcement, and process-focused supervision as pathways to strengthening integrity and reducing petty corruption in university administrative settings